Office hysteroscopy prior to ART cycle-analysis and outcome at a private IVF clinic setup in Surat, Gujarat, India - Mahale, Meeta Mohan; Nadkarni, Purnima Kishore; Nadkarni, Kishore Mohan; Singh, Pooja Prabhakar; Nadkarni, Aditi Akshay; Singh, Prabhakar Mahendra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysteroscopy is a gold standard test for assessing the uterine cavity. The presence of uterine pathology may negatively affect the chance of implantation .This study investigated the use of routine office hysteroscopy and correction of any intrauterine pathologies prior to starting IVF cycle on treatment outcome in women seeking IVF treatment for primary infertility and recurrent implantation failure. Methods: This was a retrospective study of 100 women who attended our infertility clinic from July 2016 to December 2016 and who were willing for office hysteroscopy. The main outcomes measured were clinical pregnancy rates achieved in the index IVF cycle, multiple pregnancy rate, ectopic pregnancy rate, miscarriage rate and failure rate. Results: Of the 100 patients who participated in the study, 75 patients conceived, 25 patients failed to conceive. 80.64% patients with normal findings on diagnostic hysteroscopy conceived after the procedure, 58.33% patients conceived after polypectomy, 68.42% conceived after septal resection, 71.42% conceived after adhesiolysis, 50% conceived after lateral metroplasty and 73.07% of recurrent implantation failure conceived after local endometrial injury was done on hysteroscopy. Conclusions: Hysteroscopy in infertile women prior to their IVF cycle when performed atleast 3 months in advance could improve treatment outcome.